(untitled) (Global Journal of Science Frontier Research, 2016)
There are different types of energy sources: traditional, commercial, primary, renewable and the new energy sources. The new energy sources, from the perspective of this paper are those that have been innovated in the recent past and are still being innovated by the scientists and technologists to meet the energy challenges. The availability of the fossil fuels or the commercial sources: coal, oil and gas is finite. Human beings have already used a considerable portion of the reserves. The reserves are maturing. Besides, these sources cause environmental pollutions: particulates, acid rains, toxic pollutants, particularly greenhouse gases. The greenhouse gases are warming up the globe with consequent climatic changes. Global warming and climatic change is presently one of the major challenges before human race.